An analysis of organisational culture in a restaurant in Grahamstown, South Africa - Kamona, Oabona Bonnie (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
This study investigates organisational culture and shared values that currently exist at Saint's Bistro in Grahamstown along with the desired organisational culture and desired values. In particular it explores possible discrepancies between the two using the reliable and valid Competing Values Framework (CVF) and its matched scale, the Organisational Culture Assessment Instrument (OCAI) and the Shared Values Survey. McDonald and Gandz (1992: 64-67) discovered 24 shared values that correlate with modern business and where each value ties in with one of the four quadrants of the CVF. The researcher found a study conducted by Burchell and Saele (2011: 512) which is a cultural study based on the CVF working in conjunction with shared values survey to analyse a situation and it presented an improved means of investigating culture and values related facets within an organisation. The aim of this study is to examine the existing culture and subsequently make recommendations that can create alignment between what is currently experienced and what is desired in the organisation, if it is found that misalignment exists. This research presents a study using a paper based survey conducted in a restaurant in Grahamstown, South Africa. The results are based on the use of the OCAI in conjunction with organisational shared values profiles. The study revealed that there is no significant gap between the current organisational culture and the desired organisational culture within the organisation. Due to these findings, the research established that a structured strategy for maintaining the organisational culture should be developed in order to sustain the existing organisational culture that can be used when recruiting and on-boarding new employees in the future. The research is significant in that it highlighted a link between the competing values framework and the shared values survey and this will contribute to the effective analysis of organisational culture in future culture research.
Keywords: Corporate culture -- Case studies; Corporate culture -- South Africa -- Makhanda -- Case studies; Restaurants-- -- South Africa -- Makhanda -- Management; Saints Bistro (Makhanda, -- South Africa)